Analisis Yuridis Verifikasi Identitas Pasien dalam Sistem Digitalisasi Pelayanan Kesehatan di Rumah Sakit - Oktavia M. Siagian; Irsyam Risdawati; Bane Uras Sugala; Fitri Widiya Hadiati; Khairunisa Khairunisa; Sri Rahmaida; Wan Apriyanti Lubis (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital healthcare services has encouraged hospitals to adopt information technology in delivering healthcare, particularly through the implementation of Electronic Medical Records (EMR). This transformation places patient identity verification as a fundamental process to ensure accurate medical services, reliable health data, and the protection of patients' rights and personal data. This study aims to analyze the legal framework governing patient identity verification in digital healthcare services at hospitals, examine the legal significance of patient identity verification, and analyze its legal implications in the implementation of digital healthcare services. This research employed a normative legal research method using both the statutory approach and the conceptual approach. The study relied on secondary data obtained through library research, including primary, secondary, and tertiary legal materials, which were analyzed qualitatively. The findings reveal that the legal framework for patient identity verification is regulated under Law Number 17 of 2023 on Health, Law Number 27 of 2022 on Personal Data Protection, and Minister of Health Regulation Number 24 of 2022 concerning Medical Records. These regulations establish patient identity verification as an essential element in ensuring accurate healthcare services, the reliability of Electronic Medical Records, personal data protection, and legal certainty in digital healthcare services. Proper implementation of patient identity verification also strengthens hospital accountability, enhances health data security, and supports the effectiveness of the integrated Health Information System, thereby contributing to the realization of safe, high-quality, and patient-centered digital healthcare services.